Penyaluran Sarana Prasarana Pendidikan - Maila, Mariam; Dalimunthe, Mardina Tiara; Kismadani, Nabilah Dwi; Setiyani, Rika; Oktavianda, Riyan; Setiyadi, Bradley (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This article discusses the distribution of educational infrastructure, starting from the planning concept to controlling its implementation. This research outlines the steps in the process of distributing educational facilities, through data analysis and case studies, further exploring the impact of the distribution of educational funds and infrastructure on participation levels students, availability of learning facilities, and quality of teaching. This article provides in-depth insight into increasing the efficiency and effectiveness of the distribution of educational infrastructure facilities in the context of sustainable educational development.